Liquidity constraints versus loss aversion in household consumption: a simple reconciliation - Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
Various deviations from the Permanent Income consumption model with rational expectations have been discussed in the literature, including loss aversion and liquidity constraints. In the existing literature, these two types of consumption asymmetry are usually considered as mutually exclusive. Using a single data set for US personal consumption, income and wealth for the period 1953q1-2007q3, we show that evidence of either loss aversion or liquidity constraints can indeed be produced, depending on the theoretical and econometric framework applied. We then apply a synthetic asymmetric error correction model that distinguishes short-run and long-run asymmetries and helps reconcile the conflicting results from the previous literature. Our findings can also be interpreted in the context of the secular decline in the US personal savings rate before the outbreak of the financial crisis in 2007.
urn:nbn:de:101:1-201101312921
Keywords: C22; D11; D12; E21; 330; Asymmetric error correction model; consumer economics; aggregate consumption and wealth; Einkommenshypothese; Liquiditätsbeschränkung; Risikoaversion; Gesamtwirtschaftlicher Konsum; Vermögen; Sparen; Schätzung; USA